Linguistik Forensik sebagai Bahan Ajar untuk Pembelajaran Bahasa Arab - Dzakiruddin, Muhammad; Yusuf, Kamal (Universitas Negeri Jakarta, 2022)
Arabic teaching materials must be integrated with various sciences to be more adaptive in different scientific families. One of them in the field of forensics. Therefore, this study aims to see the field of forensics as one of the Arabic language teaching materials. As a result, Arabic learners can recognize and adapt to Arabic terms or vocabulary related to investigations such as medical forensics, social forensics, and criminal forensics. This research is classified as qualitative descriptive research with a content analysis method. The Arabic website Al Jazeera serves as the primary data source in this study. According to the findings of this study, various Arabic forensic vocabularies on the Al Jazeera website can be used as teaching materials in developing Arabic listening, speaking, reading, and writing skills. In addition, teaching materials containing vocabulary related to forensics can also be implemented in knowledge assessment (KI-3) and skills assessment (KI-4).